Synthesis and Antimicrobial Activity of Tri-Substituted 1,6-Dihydropyrimidines - RAMESH, B.; BHARATHI, D.R.; BASAVARAJ, H.S.; JAYADEVAIAH, K.V. (Asian Journal of Chemistry, 2010)
A series of substituted 1,6-dihydropyrimidines compounds have been synthesized by the reaction of ethylcyanoacetate, thiourea and substituted aldehydes in the presence of potassium carbonate and ethanol. Reactions have been carried out by conventional and microwave methods. The synthesized compounds are screened for their antibacterial and antifungal activity against Staphylococcus aureus, Escherichia coli and Candida albicans, Aspergillus flavus, respectively.